2015
DOI: 10.1111/jphp.12314
|View full text |Cite
|
Sign up to set email alerts
|

Realgar nanoparticle-based microcapsules: preparation and in-vitro/in-vivo characterizations

Abstract: The developed RNM demonstrated a greater potential as a delivery system for realgar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The optimal CuA‐SEN was morphologically homogenous and spherical or elliptical (Figure d) in shape with the absence of aggregation when observed under TEM. The average DS, PDI and ZP produced were 48.83 ± 1.06 nm, 0.232 ± 0.14 and −29.92 ± 1.66 mV (Table ), respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The optimal CuA‐SEN was morphologically homogenous and spherical or elliptical (Figure d) in shape with the absence of aggregation when observed under TEM. The average DS, PDI and ZP produced were 48.83 ± 1.06 nm, 0.232 ± 0.14 and −29.92 ± 1.66 mV (Table ), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The disappearance of characteristic peaks of cuminaldehyde might be ascribed to the overlapping of drug peaks with that of the excipients. [61] Physical characteristics of optimal CuA-SEN The optimal CuA-SEN was morphologically homogenous and spherical or elliptical (Figure 3d) in shape [36,73] with the absence of aggregation when observed under TEM. The average DS, PDI and ZP produced were 48.83 AE 1.06 nm, 0.232 AE 0.14 and À29.92 AE 1.66 mV (Table 2), respectively.…”
Section: Characterisation Of Cua-senmentioning
confidence: 99%
“…[77]. Additional, RBS has the same effect for other cancer cells, such as H22 cancer cells in mice [1]. …”
Section: The Antitumor Effect and Application Of Realgar Bioleaching mentioning
confidence: 99%
“…Realgar, a traditional Chinese medicine, has been applied for more than 1800 years [1] to treat skin diseases by ancient Chinese doctors. Recent studies have indicated that realgar has an obvious anticancer effect in the clinic, especially on hematological cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As described in our previous study, the ball milling equipment (PM 100, Retsch, German) was used to formulate the realgar powder into the realgar nanoparticles (RN, mean size 85.4 AE 3.5 nm), which were further converted into the RN-based microcapsules (RNM) to improve the stability. The RNM exhibited a considerably higher release of As 2 S 2 , bioavailability, and antitumor efficacy than the crude realgar did (Shi et al, 2015). The FMO unit was processed using a high-pressure homogenization method.…”
Section: Introductionmentioning
confidence: 99%